2021
DOI: 10.3389/fpubh.2021.658243
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Awareness and Calculated 10-Year Risk Among Female Employees at Taibah University 2019

Abstract: Cardiovascular diseases (CVD) are the most common cause of death and disability worldwide. Saudi Arabia, one of the middle-income countries has a proportional CVD mortality rate of 37%. Knowledge about CVD and its modifiable risk factors is a vital pre-requisite to change the health attitudes, behaviors, and lifestyle practices of individuals. Therefore, we intended to assess the employee knowledge about risk of CVD, symptoms of heart attacks, and stroke, and to calculate their future 10-years CVD risk. An epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Unfortunately knowledge and awareness of CVD and CCS risk factors remains relatively limited in the Saudi population [ 112 , 113 ], highlighting the need for population-wide as well as individualized awareness and educational interventions to promote a healthy lifestyle.…”
Section: Results - Consensus Statementsmentioning
confidence: 99%
“…Unfortunately knowledge and awareness of CVD and CCS risk factors remains relatively limited in the Saudi population [ 112 , 113 ], highlighting the need for population-wide as well as individualized awareness and educational interventions to promote a healthy lifestyle.…”
Section: Results - Consensus Statementsmentioning
confidence: 99%
“…In the Hail region, Saudi Arabia a cross sectional study carried out among 537 participants revealed that Awareness of TV watching (88.5%), smoking (87.9%), lack of physical activities (78.4%) and family history of CAD (74.7%) as the leading cause of CAD has a distinguished higher percentage among the studied population however the family history of diabetes mellitus (51.6%), having diabetes mellitus (57.7%), family history of hypertension (65.7%) and family history of hyperlipidemia (69.1%) have the lowest percentages (Shahid et al, 2020) In Medina, Saudi Arabia. A descriptive cross-sectional community-based study was conducted among 222 of the women aged 40 years and above who are current employees at Taibah University; the results show that participants shown knowledge about unhealthy (Diabetic, 61%), (stress/anxiety, 67%), (lack of exercise, 71%), (hypertension, 80%), (overweight, 79%), (smoke, 77%), (high cholesterol, 75%) and (diet 85%) as a most common CVD risk factor (Qasem Surrati et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We compared our results with those of similar studies carried out worldwide in King Faisal University, University of Jos, Taibah University, and University of Brasilia [ 12 , 59 , 60 , 61 ]; the prevalence of hypercholesterolaemia was considerably higher in our study than in Taibah University (43,2% vs. 23.4%), while the prevalence of hypertension was lower than in the King Faisal University, University of Jos, Taibah University, and University of Brasilia studies (19.6% vs. 22.1%, 48.5%, 52.7%, and 27.5%, respectively). The same studies found higher prevalence of smoking and sedentarism than in our population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is an increasing tendency towards the prevalence of CVD in developed countries, due to increased salt consumption, reduced physical activity, and lowered levels of health literacy [ 8 ]. However, university-staff-based studies have shown that they share very similar risk factors for CVD such as obesity [ 9 ], physical inactivity [ 10 , 11 ], and smoking [ 12 ]. Recently, there was a study about the prevalence of hypertension in Brazil, which showed that 58.3% of university employees self-reported obesity as the most frequently occurring comorbidity [ 13 ].…”
Section: Introductionmentioning
confidence: 99%